Environmental education: The development of a curriculum through 'grass roots' reconstructive action - Rob O'Donoghue; Carmel McNaught (Environmental Association of Southern Africa, 1989)
The case study reported in this paper started as a research and development initiative to improve environmental education and ecology fieldwork activities. A package of resource materials and activities was developed and pilot tested with teachers. Despite highly commended workshops, however, follow-up evaluation revealed that the curriculum packages were not widely used. The paper discusses a two year action research investigation of conceptual, evaluation and adoption tensions that led to a revised approach to environmental education and curriculum innovation. The rational and centre-to-periphery orientation of the initial research and development project was replaced by a teacher support network to facilitate 'grass roots' reconstructive action. This orientation was then investigated with two groups of science teachers in rural schools. The study revealed how external support services and a sustained dialogue around the prevailing science curriculum, local environmental issues and everyday classroom activities fostered reconstructive change at a local level. The transition from an external and rational strategy of curriculum development to a networking service in support of local reconstructive action is described. Some of the emerging management and design considerations for a revised political economy (policy and action framework) of environmental education curriculum change are discussed.